Answer:
![log_3_2(5)=\frac{1}{5} k](https://tex.z-dn.net/?f=log_3_2%285%29%3D%5Cfrac%7B1%7D%7B5%7D%20k)
Step-by-step explanation:
Let's start by using change of base property:
![log_b(x)=\frac{log_a(x)}{log_a(b)}](https://tex.z-dn.net/?f=log_b%28x%29%3D%5Cfrac%7Blog_a%28x%29%7D%7Blog_a%28b%29%7D)
So, for ![log_2(5)](https://tex.z-dn.net/?f=log_2%285%29)
![log_2(5)=k=\frac{log(5)}{log(2)}\hspace{10}(1)](https://tex.z-dn.net/?f=log_2%285%29%3Dk%3D%5Cfrac%7Blog%285%29%7D%7Blog%282%29%7D%5Chspace%7B10%7D%281%29)
Now, using change of base for ![log_3_2(5)](https://tex.z-dn.net/?f=log_3_2%285%29)
![log_3_2(5)=\frac{log(5)}{log(32)}](https://tex.z-dn.net/?f=log_3_2%285%29%3D%5Cfrac%7Blog%285%29%7D%7Blog%2832%29%7D)
You can express
as:
![2^5](https://tex.z-dn.net/?f=2%5E5)
Using reduction of power property:
![log_z(x^y)=ylog_z(x)](https://tex.z-dn.net/?f=log_z%28x%5Ey%29%3Dylog_z%28x%29)
![log(32)=log(2^5)=5log(2)](https://tex.z-dn.net/?f=log%2832%29%3Dlog%282%5E5%29%3D5log%282%29)
Therefore:
![log_3_2(5)=\frac{log(5)}{5*log(2)}=\frac{1}{5} \frac{log(5)}{log(2)}\hspace{10}(2)](https://tex.z-dn.net/?f=log_3_2%285%29%3D%5Cfrac%7Blog%285%29%7D%7B5%2Alog%282%29%7D%3D%5Cfrac%7B1%7D%7B5%7D%20%5Cfrac%7Blog%285%29%7D%7Blog%282%29%7D%5Chspace%7B10%7D%282%29)
As you can see the only difference between (1) and (2) is the coefficient
:
So:
![\frac{log(5)}{log(2)} =k\\](https://tex.z-dn.net/?f=%5Cfrac%7Blog%285%29%7D%7Blog%282%29%7D%20%3Dk%5C%5C)
![log_3_2(5)=\frac{1}{5} \frac{log(5)}{log(2)} =\frac{1}{5} k](https://tex.z-dn.net/?f=log_3_2%285%29%3D%5Cfrac%7B1%7D%7B5%7D%20%5Cfrac%7Blog%285%29%7D%7Blog%282%29%7D%20%3D%5Cfrac%7B1%7D%7B5%7D%20k)
Answer:
(6, -3)
Step-by-step explanation:
The actual coordinates are x = -6 and y = 3
If we rotate 180 degrees and the center of rotation is at (0,0), all we need to do is invert the signal of each axis, that is, we invert the sign of the original x-coordinate and invert the signal of the original y-coordinate.
So the final x-coordinate is - (-6) = 6
And the final y-coordinate is - (3) = -3
So the coordinates will be (6, -3).
Answer:24 and 10
Step-by-step explanation:24-10=34 24-10=14
Answer:
18
Step-by-step explanation:
For this problem, we will simply plug in the values of a and b into the respective variables in the expression 3ab to "evaluate" the expression.
a = 2; b = 3
3ab
Note, that when variables like a and b are smashed with a constant, the use of multiplication is in play.
3ab = 3 * a * b
With this in mind, let's plug in the values of a and b into the expression.
3ab
= 3 (2) (3)
= 3 (6)
= 18
Hence, 3ab evaluated when a=2 and b=3 is 18.
Cheers.
Answer: D.
Step-by-step explanation:
The associative property of addition states that numbers can be added together regardless of how they are grouped.
Answer A shows a property of multiplication.
Answer B shows the additive identity property.
Answer C shows the commutative property.
However, answer D shows that the numbers can be added regardless of how they are grouped.